Benjamin's box : the story of the Resurrection Eggs - Carlson, Melody; Rainey, Barbara; Stockman, Jack, 1951-; Veldheer, Mark; Zonderkidz (Grand Rapids, Mich. : Zonderkidz, 2008)
A young boy follows Jesus through Jerusalem, collecting mementos in his treasure box to share with others and to remind him of Jesus's teachings.
Originally published: Sisters, Or. : Gold'n'Honey Books, 1997.
"Cover & interior design: Mark Veldheer."--Page opposite title page.
004-007.
Keywords: Easter stories; Jesus Christ -- Resurrection -- Juvenile fiction; Resurrection -- Biblical teaching -- Juvenile fiction; God -- Worship and love -- Juvenile fiction; Boys -- Juvenile fiction; Jerusalem -- Juvenile fiction; Jesus Christ -- Resurrection -- Fiction; Easter -- Fiction